Research on the evolutionary game of safety behavior of EPC consortium members based on prospect theory - Zeyou Chen; Liang Xia; Yangyang Su; Guangran Chen; Zheyuan Zhang (Journal of Asian Architecture and Building Engineering)
In recent years, the consortium, composed of the design enterprise, construction enterprise, and supplier, has witnessed rapid development in implementing the EPC project model in China. However, there are conflicts of interest and ambiguous safety management among EPC consortium members, leading to accidents. This study aims to explore the decision-making process regarding different safety behavior strategies among EPC consortium members. Given the uncertainty of the EPC project environment, consortium members show risk preferences and perceptual biases. Prospect theory reveals the irrational elements in the decision-making process. Therefore, this study incorporates prospect theory, constructs a safety behavior perception payoff matrix and an evolutionary game model involving design enterprise, construction enterprise, and supplier as the primary stakeholders, analyzes the interactive mechanisms of safety behavior among the three parties, and uses MATLAB simulation to explain the evolutionary path of behavioral strategies under varying parameters. The consequence indicates that the optimal strategy’s stable state in the safety behavior evolution system of EPC consortium members is affected by the players’ cognitive biases and risk preferences, and the costs of safety input, punishment intensity, and accident losses. This study mainly provides theoretical evidence and decision support for safety control activities among EPC consortium members.